Reducing perioperative red blood cell unit issue orders, returns, and waste using failure modes and effects analysis. Issue 4 (8th February 2023) - Lou, Sunny S.; Dewey, Megan M.; Bollini, Mara L.; Harford, Derek R.; Ingold, Cindy; Wildes, Troy S.; Stevens, Tracey W.; Martin, Jackie L.; Grossman, Brenda J.; Kangrga, Ivan
Abstract: Background: Surgical transfusion has an outsized impact on hospital‐based transfusion services, leading to blood product waste and unnecessary costs. The objective of this study was to design and implement a streamlined, reliable process for perioperative blood issue ordering and delivery to reduce waste. Study Design and Methods: To address the high rates of surgical blood issue requests and red blood cell (RBC) unit waste at a large academic medical center, a failure modes and effects analysis was used to systematically examine perioperative blood management practices. Based on identified failure modes (e.g., miscommunication, knowledge gaps), a multi‐component action plan was devised involving process changes, education, electronic clinical decision support, audit, and feedback. Changes in RBC unit issue requests, returns, waste, labor, and cost were measured pre‐ and post‐intervention. Results: The number of perioperative RBC unit issue requests decreased from 358 per month (SD 24) pre‐intervention to 282 per month (SD 16) post‐intervention ( p  < .001), resulting in an estimated savings of 8.9 h per month in blood bank staff labor. The issue‐to‐transfusion ratio decreased from 2.7 to 2.1 ( p  < .001). Perioperative RBC unit waste decreased from 4.5% of units issued pre‐intervention to 0.8% of units issued post‐intervention ( p  < .001), saving an estimated $148, 543 in RBC unit acquisition costs and $546, 093 in overhead costs per year. Discussion: Our intervention, designed based on a structured failure modes analysis, achieved sustained reductions in perioperative RBC unit issue orders, returns, and waste, with associated benefits for blood conservation and transfusion program costs.